Consumer payment choice: Merchant card acceptance versus pricing incentives - Arango, Carlos; Huynh, Kim P.; Sabetti, Leonard (Journal of Banking & Finance, 2015)
Using transaction-level data from a three-day shopping diary, we estimate a model of consumer payment instrument choice that disentangles the effect of merchant card acceptance from credit card pricing incentives (rewards) at the point-of-sale. The lack of merchant card acceptance plays a large role in the use of cash, especially for low-value transactions (less than 25dollars). Participation in a credit card rewards program induces a shift toward credit card usage at the expense of both debit cards and cash. In contrast, changes in the amount of rewards (ad valorem) has a small or inelastic effect on the probability of paying with credit cards. Our findings highlight the importance of the two-sided nature of retail payment systems and provide key insights into consumer and merchant behaviour.